ANALISIS MAKNA DENOTATIF DAN KONOTATIF DALAM FILM UPIN & IPIN EPISODE KENANGAN MENGUSIK JIWA - Juprinedi, Juprinedi; Siahaan, Arta Uly; Miranto, Cahya (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2020)
Representations of public life in recalling past events or history can be found, among others, in 3D animated films. An interpretation of connotative meaning, as the second layer meaning, arises when a symbol is associated with its psychological aspects, such as feelings, emotions, or beliefs, which are closely related to culture, knowledge, and history. This study aims to interpret symbols in the Kenangan Mengusik Jiwa episode of Upin & Ipin animated film for their denotative and connotative meaning to better understand the context of the story and the moral message conveyed. A questionnaire was used in this research to increase validity. In processing questionnaire data, a calculation is conducted using the Likert scale. The results of the study indicate that the main moral message conveyed in this episode is to never forget history or established culture. This interpretation is supported by results from questionnaire data.